The three dimensions of archaeology : proceedings of the XVII UISPP World Congress (1-7 september, Burgos, Spain). - Kamermans, Hans,; Neef, Wieke de,; Piccoli, Chiara,; Posluschny, Axel G.,; Scopignio, Robert, (Archaeopress archaeology., 2016)
This volume brings together presentations from two sessions organized for the XVII World UISPP Conference: The scientific value of 3D archaeology, and Detecting the Landscape(s).